The Role of Granting Expert Information By The Indonesian Financial Examiner's Loss on the Judge's Decision In Proof of Criminal Offense - Sultan Sa'aduddin Akib; Andi Muhammad Sofyan; Audyna Mayasari Muin (IHSA Institute, 2022)
The study aims to analyze the role of expertory by the Indonesian finance ministry on assessing the state's losses to the judges decision on alleged criminal corruption and the obstacles it faced by the finance ministry's giving expert testimony in judicial proceedings. The type of research used by the writer is the type of empirical law study. The study is conducted at the finance ministry of the Indonesian Republic of Sulawesi representative and the makassar district court. The legal material used is the primary law ingredient, the data obtained directly from interviews and secondary law materials, data through literature, books, journals, and legislation studies. The material of the law is qualitatively analyzed and presented in descriptive terms. The results of the research, concluded that, (1) The role of giving expert information by BPK is important but evidence is not binding on the judge to render a ruling. So that the judge has the right and freedom to make an appraisal of his perfection and truthfulness, and the judge can either accept, regard and make into consideration the giving of expert information by the body of the financial examiner or not. (2) In general, there are 2 (two) obstacles to proving a link to the criminal corruption, which is a drawback to the country's limited human resources, time for checkups and budgets. And also obstacles during the process of giving expert explanations that include, psychological obstacles, communication barriers, inappropriate congregation schedules, impaired professional health, and lack of material mastery by the expert.